The genus Metaporcelaimus Lordello, 1965 (Nematoda, Dorylaimida, Aporcelaimidae) in Ukraine: Description of one known and two new species without hiatus - Krainer, Liubomyr; Susulovsky, Andrij; Peña-Santiago, Reyes (Zootaxa, 2018)
One known (M. romanicus) and two new species of the genus Metaporcelaimus, collected in natural and semi-natural habitats of Ukraine, are described and illustrated. Metaporcelaimus concinnus sp. n. is characterized by its 3.09–4.58 mm long body, lip region 16.5–19.5 µm broad and visibly wider than the adjacent body, odontostyle 17–19 µm long, neck 745–865 µm long, pharyngeal expansion occupying 62–66% of total neck length, uterus tripartite and 3.9–5.7 times the corresponding body diameter, vulva longitudinal (V = 49–53%), tail conical (44–54 µm, c = 67–94, c’ = 1.0–1.3 in females), spicules 79–86 µm long with strongly bifurcate distal end, and 10–14 irregularly spaced ventromedian supplements without hiatus. Metaporcelaimus declivicaudatus sp. n. is characterized by its 2.88–3.66 mm long body, lip region 23–28 µm broad, odontostyle 24–26 µm long, neck 634–788 µm long, pharyngeal expansion occupying 48–56% of total neck length, uterus tripartite and 3.0–3.4 times the corresponding body diameter long, vulva transverse (V = 51–55%), tail conical (45–65 µm, c = 53–63, c’ = 1.0–1.2) with rounded terminus, spicules 102–113 µm long, and 12–14 spaced ventromedian supplements without hiatus. New information about M. romanicus is also provided, confirming available data about this species.